(untitled) (UNIZIK Journal of Educational Management and Policy, 2024)
This study aimed to ascertain the impact of Information and Communication Technology (ICT) on teaching of science in senior secondary schools in Awka South local government area of Anambra State. Two research questions were raised and answered to achieve the purpose of this study. A descriptive survey research design was used to carry out this study. The population for this study consisted of all the 116 science teachers in 19 public senior secondary schools in Awka South local government of Anambra State The total population sampling method was used for the study which gave a sample size of 116 science teachers. The instrument used for collection of data is a structured questionnaire developed by the researchers. The questionnaire contained thirteen (13) item questions. The instrument was validated by three (3) lecturers from the Department of Science Education, Nnamdi Azikiwe University, Awka. To determine the internal consistency of the instrument, Cronbach alpha method was used and a reliability coefficient of 0.89 was obtained. The researchers with the aid of 5 research assistants went to the sample public senior secondary schools and administered the questionnaire to the respondents on the spot. Data collected were analyzed using mean. Results revealed that ICT has a positive impact on the academic achievement of students in science. The result of the study also revealed that information and communication technology equipment are not readily available or complete in schools. It was recommended among others that government should provide funding and adequate ICT equipment for schools to use in order to aid learning